2023
DOI: 10.1111/jcpe.13854
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of periodontitis diagnosis obtained using multiple molecular biomarkers in oral fluids: A systematic review and meta‐analysis

T. Blanco‐Pintos,
A. Regueira‐Iglesias,
I. Seijo‐Porto
et al.

Abstract: AimTo determine the accuracy of biomarker combinations in gingival crevicular fluid (GCF) and saliva through meta‐analysis to diagnose periodontitis in systemically healthy subjects.MethodsStudies on combining two or more biomarkers providing a binary classification table, sensitivity/specificity values or group sizes in subjects diagnosed with periodontitis were included. The search was performed in August 2022 through PUBMED, EMBASE, Cochrane, LILACS, SCOPUS and Web of Science. The methodological quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“… 75 Also, as demonstrated by a very recent meta-analysis, the accuracy of early periodontitis diagnosis can be strongly increased through detection of IL-1β in combination with other biomarkers in saliva. 76 In particular, combination of IL-1β with MMP-8, or with IL-6, and IL-6 with MMP-8 measurements would allow correct identification of 78%–81% of periodontitis patients and the exclusion of 85–88% of non-periodontitis subjects. Unfortunately, the level of salivary components is rarely determined in oral and systemic clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 75 Also, as demonstrated by a very recent meta-analysis, the accuracy of early periodontitis diagnosis can be strongly increased through detection of IL-1β in combination with other biomarkers in saliva. 76 In particular, combination of IL-1β with MMP-8, or with IL-6, and IL-6 with MMP-8 measurements would allow correct identification of 78%–81% of periodontitis patients and the exclusion of 85–88% of non-periodontitis subjects. Unfortunately, the level of salivary components is rarely determined in oral and systemic clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…to refer patients to specialist periodontists for professional diagnosis and effective care (Blanco-Pintos et al, 2023). Moreover, POCT kits allow for individualized treatment plans, reducing the risk of over-or under-treatment, and offer an efficient and accurate method to determine the prevalence of periodontitis in epidemiological surveys compared to time-consuming full-mouth exams (Gul et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…CRS is a cumulative analysis method of bacteria-and host-derived biomarkers, which are composed of the salivary levels of P. gingivalis, IL-1β and MMP-8 (Gursoy et al, 2011). Recent systematic reviews have indicated that salivary biomarkers have acceptable performance characteristics such as high sensitivity, specificity and predictive values (Arias-Bujanda et al, 2020;Blanco-Pintos et al, 2023;Sánchez-Medrano et al, 2023). Indeed, our group has successfully demonstrated that the cumulative use of biomarkers with an adaptive design has significant superiority over single biomarkers with respect to accuracy and has also validated the diagnostic accuracy of CRS in studies with unrelated populations (Gursoy et al, 2018;Salminen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%